Accuracy of the Helicobacter pylori diagnostic tests in patients with peptic ulcer bleeding: a systematic review and network meta-analysis. (December 2020) - Vörhendi, Nóra; Soós, Alexandra; Anne Engh, Marie; Tinusz, Benedek; Szakács, Zsolt; Pécsi, Dániel; Mikó, Alexandra; Sarlós, Patrícia; Hegyi, Péter; Eröss, Bálint
Introduction: Some studies suggest that the accuracy of Helicobacter pylori diagnostic tests is decreased in peptic ulcer bleeding (PUB). We aimed to assess the accuracy of diagnostic tests for H. pylori in patients with PUB in a diagnostic test accuracy (DTA) network meta-analysis. Methods: A systematic search was carried out in seven databases until November 2019. We collected or calculated true and false positive and negative values, and constructed 2×2 diagnostic contingency tables with reference standards including histology, rapid urease test, urea breath test, serology, stool antigen test, culture, and polymerase chain reaction. We ranked the index tests by the superiority indices (SI) and calculated pooled sensitivity and specificity of each test. Discussion: Our search yielded 40 eligible studies with 27 different diagnostic strategies for H. pylori . In 32 articles, the reference standard was a combination of multiple tests. In 12 studies, the index tests were compared with a single testing method. We analyzed seven networks with the reference standards against a single or a combination of diagnostic index tests. None of the index tests had better diagnostic accuracy (SI between 9.94 and 2.17) compared with the individual index tests as all the confidence intervals included 1. Combined testing strategies had higher sensitivities (0.92–0.62) and lower specificities (0.85–0.46) while single tests proved to have higher specificities (0.83–0.77) and lower sensitivities (0.73–0.42). Conclusion: Use of combined tests may have a rationale in clinical practice due to their higher sensitivities. The differences between the included DTA studies limited the comparison of the testing strategies.